2018
DOI: 10.1039/c8dt02614a
|View full text |Cite
|
Sign up to set email alerts
|

Low valent Al(ii)–Al(ii) catalysts as highly active ε-caprolactone polymerization catalysts: indication of metal cooperativity through DFT studies

Abstract: The present study first describes the reactivity of low valent Al(ii) and Ga(ii) complexes of the type (dpp-bian)M-M(dpp-bian) (1, M = Al; 2, Ga; dpp-bian2- = 1,2-bis-(2,6-iPr2-C6H3)-acenaphthenequinonediamido) with cyclic esters/carbonates such as ε-caprolactone (CL) and trimethylene carbonate (TMC). CL and TMC both readily coordinate to the Al(ii) species 1 to form the corresponding bis-adducts (dpp-bian)Al(L)-(L)Al(dpp-bian) (3, L = CL; 4, L = TMC), which were structurally characterized confirming that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The use of chelating ligand allowed to obtain binuclear Al (II) complex 23 (Figure 6) with specific chemistry and catalytic properties [69]. It was found that 23 reacts with two equivalents of εCL with a formation of relatively stable adduct, its structure was confirmed by X-ray diffraction analysis.…”
Section: Coordination Polymerization Of Lactonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of chelating ligand allowed to obtain binuclear Al (II) complex 23 (Figure 6) with specific chemistry and catalytic properties [69]. It was found that 23 reacts with two equivalents of εCL with a formation of relatively stable adduct, its structure was confirmed by X-ray diffraction analysis.…”
Section: Coordination Polymerization Of Lactonesmentioning
confidence: 99%
“…As demonstrated in a number of publications, heteroleptic metal alkoxides form stable binuclear complexes [69,94,97,99,140,147,148,149] that are able to catalyze ROP of cyclic esters by both binuclear and mononuclear mechanisms. DFT modeling has been shown to be an effective instrument of choice of the preferable reaction pathway.…”
Section: Coordination Polymerization Of Lactides and Glycolidementioning
confidence: 99%
“…1.317(4) Å, respectively). In this way, dpp‐bian in compounds 2 and 3 constitutes a dianionic reduced form, whereas in 4 the ligand has a radical‐anionic character as inferred from the diagnostic C–N and C–C bond lengths, which are intermediate between those in neutral dpp‐bian (1.282(4) Å and 1.534(6) Å, respectively) and (dpp‐bian) 2– in 2 and 3 and other similar compounds , , …”
Section: Resultsmentioning
confidence: 97%
“…Recently, we demonstrated that the chelate ene‐bisamide form of the ligand dpp‐bian (=1,2‐bis[(2,6‐diisopropylphenyl)imino]acenaphthene) readily stabilizes the d 0 configuration of the titanium atom with the formation of the chlorido complex [(dpp‐bian)TiCl 2 ] 2 , which appears to be an easy‐to‐use precursor for further dpp‐bian‐supported titanium derivatives. It should be noted that magnesium and calcium complexes of dpp‐bian have proved to be robust catalysts for the ROP of L ‐ and rac ‐lactides, forming PLAs which are non‐toxic toward human fibroblasts, while the binuclear aluminum compound [(dpp‐bian)Al] 2 was found to be an extremely active initiator of the controlled ROP of ε‐caprolactone at room temperature . In an effort to expand the scope of non‐toxic catalytic systems based on dpp‐bian for the polymerization of cyclic esters, we report on the synthesis and catalytic activity of titanium alcoholates stabilized with dianionic and radical anionic forms of dpp‐bian, in the ROP of L‐lactide (LA) .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the hydroarylation with phenylacetylene was possible with 30 as catalyst (Figure a), but not with digallane 62 . Moreover, dialane 30 rendered suitable as a catalyst for the ring‐opening polymerization of ε‐caprolactone (Figure b) . Employing 30 as the sole catalyst resulted in low catalytic activity since it reacted with the substrate to form the bis‐adduct 42 .…”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 99%